2022
DOI: 10.1021/acsearthspacechem.2c00039
|View full text |Cite
|
Sign up to set email alerts
|

On the Complementarity and Informative Value of Different Electron Ionization Mass Spectrometric Techniques for the Chemical Analysis of Secondary Organic Aerosols

Abstract: The atmospheric aging of volatile organic compounds leads to the formation of complex mixtures of highly oxidized secondary organic aerosols (SOAs). State-of-the-art mass spectrometry (MS) has become a pivotal tool for their chemical characterization. In this study, we characterized the chemical complexity of naphthalene-derived SOA by three different time-of-flight (TOF) mass spectrometric techniques applying electron ionization: high-resolution–TOF–aerosol MS (AMS), direct inlet probe (DIP)–high-resolution T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Other oxygenated aerosol particle constituents reveal temporally different concentration profiles and steadily increase or peak after the first photochemical ageing or after dark ageing. For example, C 10 H 6 O 2 (naphthoquinone), formed from the oxidation of naphthalene, 90 shows its maximum after the first photochemical ageing for both flaming and smouldering BB aerosols. However, many oxygenated species detected by the APPI FT-ICR-MS peak in relative concentrations for the flaming aerosol, but steadily increase during ageing of the smouldering BB aerosol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other oxygenated aerosol particle constituents reveal temporally different concentration profiles and steadily increase or peak after the first photochemical ageing or after dark ageing. For example, C 10 H 6 O 2 (naphthoquinone), formed from the oxidation of naphthalene, 90 shows its maximum after the first photochemical ageing for both flaming and smouldering BB aerosols. However, many oxygenated species detected by the APPI FT-ICR-MS peak in relative concentrations for the flaming aerosol, but steadily increase during ageing of the smouldering BB aerosol.…”
Section: Resultsmentioning
confidence: 99%
“…The exported mass spectra were processed by using selfwritten MATLAB algorithms and routines combined in a graphical user interface named CERES Processing. Aer careful investigation and taking into account attribution boundaries from the literature, the following restrictions were deployed for elemental composition assignment for ESI-Orbitrap-MS in the range of 90 For APPI-FT-ICR-MS the following attribution boundaries were applied:…”
Section: Environmental Science: Processes and Impacts Papermentioning
confidence: 99%
“…To resolve the large number of constituents of highly complex OAs, thermal desorption comprehensive two-dimensional gas chromatography hyphenated with time-of-flight mass spectrometry (TD–GC × GC–TOFMS) has been shown to be useful for chemical fingerprinting of the (semi)volatile organic fraction in PM. 26 As a powerful separation technique, GC × GC–MS has been used in several studies 15 , 27 29 to effectively detect a wide range of compounds found in BBOAs. For the analysis of GC × GC–MS data, one typically differs between targeted and untargeted analysis.…”
Section: Introductionmentioning
confidence: 99%